Functional interaction of melatonin with gasotransmitters and ROS in plant adaptation to abiotic stresses - Kolupaev, Yuriy E.; Yemets, Alla; Yastreb, Tetiana O.; Blume, Yaroslav (Frontiers in Plant Science, 2024)
Melatonin is considered a multifunctional stress metabolite and a novel plant hormone affecting seed germination, root architecture, circadian rhythms, leaf senescence, and fruit ripening. Melatonin functions related to plant adaptation to stress stimuli of various natures are considered especially important. One of the key components of melatonin's stress-protective action is its ability to neutralise reactive oxygen species (ROS) and reactive nitrogen species directly. However, many of its effects are related to its involvement in the signalling network of plant cells and its influence on the expression of a large number of genes important for adaptation to adverse factors. Insights into the functional relationships of melatonin with gasotransmitters (GT)gaseous molecules performing signalling functions -are still emerging. This review has analysed and summarised the experimental data that testify to the participation of the main GTs -nitric oxide, hydrogen sulfide, and carbon monoxide -in the implementation of the protective effect of melatonin when plants are exposed to abiotic stimuli of various nature. In addition, modulation by melatonin of one of the most important components in the action of GTs and ROS -post-translational modifications of proteins and the influence of ROS and GTs on melatonin synthesis in plants under stress conditions and the specific physiological effects of exogenous melatonin and GTs have been reviewed. Finally, the prospects of the GTs' practical application to achieve synergistic stress-protective effects on plants have been considered.